Strategi Kepala Sekolah Dalam Meningkatkan Prestasi Akademik Siswa Di Smp Muhammadiyah 3 Gorontalo - Mokoagow, Kurniati; R. Mala, Abdurrahman; Sidik, Firman (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study is to determine: 1) the principal's strategy in improving student academic achievement at SMP Muhammadiyah 3 Gorontalo; 2) the supporting and inhibiting factors in improving student academic achievement at SMP Muhammadiyah 3 Gorontalo. This research is qualitative in nature, with the subjects being the principal, teachers, and students. Data collection techniques include observation, interviews, and documentation. The research findings indicate that: 1) The principal's strategies include improving the planning, implementation, and supervision systems, as well as evaluation of the school; fostering good cooperation with all teachers and staff; and implementing policies deemed capable of enhancing the educational system; 2) Improving student learning performance involves continuously motivating and inspiring teachers, staff, and students, as well as providing adequate facilities and infrastructure supported by learning resources; 3. Supporting factors in improving student performance include a system of cooperation and professionalism in performing duties, support for facilities and infrastructure, and the principal's concern for the development of the education system at the school, as well as support from relevant parties in supporting the programs implemented at the school. Meanwhile, the inhibiting factors include the lack of communication with parents, especially those whose homes are far from the school, making it difficult for the school to directly monitor student progress. Additionally, some students occasionally violate school rules and policies, overwhelming teachers in their efforts to improve academic performance